Aqueous root extract of Salacia oblonga ameliorates experimental diabetes by upregulation of PDX1 expression and alpha-to-beta cell trans-differentiation - Senthil Kumar Anbumani, Abarajitha Shankaranarayanan, Jones Eben Raj Thomson, Santhosh Sadayan, Manickam Subramanian (Journal of Applied Pharmaceutical Science, 2025)
The global rise in diabetes has spurred interest in plant-based treatments. The plant Salacia oblonga exhibits antidiabetic activity by inhibiting alpha-glucosidase and stimulating insulin secretion. The transcription factor pancreatic and duodenal homeobox 1 (PDX1) is vital for beta cell stimulation, neogenesis, and insulin secretion. This study evaluated the impact of Salacia oblonga on insulin and glucagon secretion and PDX1 expression. Streptozotocin-induced male Wistar albino diabetic rats received glibenclamide (2 mg/kg) and aqueous extract of S. oblonga root (200 mg/kg) orally for 8 weeks. Fasting blood glucose, insulin, glucagon, lipid profiles, and renal markers, were analyzed. Histopathology, immunohistochemistry, and PDX1 protein and gene expression in the pancreas were also assessed. Salacia oblonga significantly reduced fasting blood glucose and enhanced insulin and glucagon secretion in diabetic rats. Histopathology and immunohistochemistry confirmed recovery from streptozotocin-induced damage and increased numbers of beta and alpha cells. Quantitative polymerase chain reaction and western blot analyses showed upregulation of PDX1 expression. Increased alpha cell mass and glucagon and insulin expression indicated alpha-to-beta cell trans-differentiation. Salacia oblonga root extract exhibited antidiabetic properties by upregulating PDX1 expression and promoting alpha-to-beta cell trans-differentiation. It also corrected fat and protein metabolism disturbances, highlighting its potential in preventing diabetic complications and making it a promising candidate for further diabetes research.
Keywords: Diabetes, Salacia oblonga, PDX1, trans-differentiation, insulin, glucagon